Designing water protection zones using GIS tools - Zaiachkivska, B.; Denysiuk, B.; Burbyha, Ya. (Land Management, Cadastre and Land Monitoring, 2025)
The regulatory and legal principles of designing water protection zones and their role in protecting the natural environment, determining the boundaries of coastal protection strips and the influence of relief on the size of restriction zones are analyzed. The territory of the Kamianopotokivska territorial community in the Kremenchuk district of the Poltava region is studied. The water bodies in the study area were classified, and the normative values of coastal protection strips were determined based on their sizes, in accordance with current legislation requirements. Based on open data on the relief of the territory, slopes were calculated and doubling of coastal protection strips within slopes exceeding 3 degrees was provided.A geospatial dynamic model for designing water protection zones, taking into account legislative norms and terrain and their impact on activities, has been developed. The model was created and tested using the Model Builder software module in ArcGIS Pro.As a result of the study, the geospatial model  was applied to the collected input data and water protection zones were designed within the study area. The territories were identified and analyzed, the ownership rights of which are encumbered in accordance with the designed water protection zones. This model is dynamic and suitable for use for production purposes at the local level (within territorial communities).Key words: water protection zone; coastal protective strip; territorial community; water bodies; design of water protection zones; GIS technologies; geoinformation systems.